ASSESSMENT OF HEAVY METALS IN MUSHROOM SPECIES OBTAINED IN AKURE, NIGERIA - Abulude, Francis O; Ndamitso, Mohammed M (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2018)
The aim of this study was to determine the heavy metal concentrations of seven mushroom species obtained in Akure, a town in Southwest of Nigeria. The samples were preprocessed, ashed, dissolved in distilled water with drops of HCl, filtered and the resultant solution was used in the analysis. The values obtained for Manganese was the most prominent (2.66 – 4.57mg/100g) while lead was the least (0.60 – 1.68mg/100g). Cadmium was not detected in all the species. Generally, from the results obtained there were no significant differences in the accumulation of individual elements by mushrooms. Comparing the values here with the recommended dietary allowances (RDA), therefore the levels of these elements are not toxic to consumers.